2002
DOI: 10.1128/iai.70.1.218-225.2002
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides from Periodontopathic BacteriaPorphyromonas gingivalisandCapnocytophaga ochraceaAre Antagonists for Human Toll-Like Receptor 4

Abstract: Toll-like receptors (TLRs) 2 and 4 have recently been identified as possible signal transducers for various bacterial ligands. To investigate the roles of TLRs in the recognition of periodontopathic bacteria by the innate immune system, a Chinese hamster ovary (CHO) nuclear factor-B (NF-B)-dependent reporter cell line, 7.7, which is defective in both TLR2-and TLR4-dependent signaling pathways was transfected with human CD14 and TLRs. When the transfectants were exposed to freeze-dried periodontopathic bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 42 publications
4
142
1
5
Order By: Relevance
“…Recent studies suggest that TLR2 might be the primary signal-transducing molecule for LPS from certain nonenterobacterial Gramnegative organisms, including P. gingivalis [9,11,12] and Leptospira interrogans [32]. However, controversy still exists in the case of P. gingivalis LPS, as it appears to also have activity for TLR4 [12,[33][34][35]. P. gingivalis LPS has been shown to antagonize the activity of TLR4 agonists [33], and several studies in fibroblasts indicate that signaling in response to P. gingivalis LPS is mediated, in part, through TLR4 [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that TLR2 might be the primary signal-transducing molecule for LPS from certain nonenterobacterial Gramnegative organisms, including P. gingivalis [9,11,12] and Leptospira interrogans [32]. However, controversy still exists in the case of P. gingivalis LPS, as it appears to also have activity for TLR4 [12,[33][34][35]. P. gingivalis LPS has been shown to antagonize the activity of TLR4 agonists [33], and several studies in fibroblasts indicate that signaling in response to P. gingivalis LPS is mediated, in part, through TLR4 [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown to antagonize Escherichia coli LPS-dependent induction of E-selectin expression, p38 MAPK activation, and NF-␣B activation in human endothelial cells and monocytes (2,3). The ability of P. gingivalis LPS to down-regulate innate immune responses to other LPS (E. coli) may play a role in allowing this oral pathogen to evade the normal surveillance system so essential in maintaining periodontal health (4). Fimbriae are reported to mediate the bacterial adherence to and invasion of epithelial cells and gingival fibroblasts (5).…”
Section: Identification Of Signaling Pathways In Macrophage Exposed Tmentioning
confidence: 99%
“…For example, LPS isolates from the oral pathogen, P. gingivalis, have been shown to antagonize E. coli LPS-dependent induction of E-selectin expression, p38 MAPK activation, and NF-B activation in human endothelial cells (22)(23)(24). P. gingivalis LPS has also been shown to inhibit E. coli LPS-stimulated release of TNF-␣, IL-␤, and IL-6 in human monocytes, as well as ICAM-1 expression in human gingival fibroblasts (25,26). Recently, our laboratory performed structural analyses of antagonistic P. gingivalis LPS preparations and found that they are comprised mainly of tetra-acylated lipid A structures (27,28).…”
mentioning
confidence: 99%
“…Recently, our laboratory performed structural analyses of antagonistic P. gingivalis LPS preparations and found that they are comprised mainly of tetra-acylated lipid A structures (27,28). The ability of antagonistic P. gingivalis LPS to down-regulate critical innate immune responses has been postulated to play an important role in this oral pathogen's ability to override the normal surveillance system that is essential to maintaining periodontal health (22,23,26,29). In addition, recent study has suggested that antagonist forms of LPS isolated from Helicobacter pylori play a role in the ability of this microbe to induce gastric inflammation (30).…”
mentioning
confidence: 99%